Real‐world experience with the all‐oral, interferon‐free regimen of ombitasvir/paritaprevir/ritonavir and dasabuvir for the treatment of chronic hepatitis C virus infection in the German Hepatitis C Registry. Issue 10 (25th May 2017) - Welzel, T. M.; Hinrichsen, H.; Sarrazin, C.; Buggisch, P.; Baumgarten, A.; Christensen, S.; Berg, T.; Mauss, S.; Teuber, G.; Stein, K.; Deterding, K.; van Bömmel, F.; et al.
Summary: Real‐world studies are relevant to complement clinical trials on novel antiviral therapies against chronic hepatitis C; however, clinical practice data are currently limited. This study investigated effectiveness and safety of ombitasvir/paritaprevir/ritonavir (OBV/PTV/r)±dasabuvir (DSV)±ribavirin (RBV) for treatment of HCV genotype (GT) 1 and GT4 infection in a large real‐world cohort. The German Hepatitis C Registry is an observational cohort study prospectively collecting clinical practice data on direct‐acting antiviral therapies. Patients with GT1/4 infection treated with OBV/PTV/r±DSV±RBV were analysed. Effectiveness was assessed by sustained virologic response in 558 patients who reached post‐treatment week 12 (SVR12). Safety is reported in 1017 patients who initiated treatment. Of the patients, 892 (88%) had GT1 and 125 (12%) had GT4 infection. Prior treatment experience and cirrhosis were reported in 598 (59%) and 228 (22%) patients, respectively. Overall, SVR12 (mITT) was 96% (486/505) in GT1‐ and 100% (53/53) in GT4 patients. SVR12 rates were high across subgroups including patients with cirrhosis (95%, 123/129), patients with moderate to severe renal impairment (100%, 34/34), and subgroups excluded from registrational trials like patients ≥70 years (96%, 64/67) and failures to prior protease inhibitor treatment (96%, 46/48). Adverse events (AEs) and serious AEs were reported in 52% (525/1017) and 2% (21/1017) of patients, respectively, and led to treatment discontinuation in 1.5% (15/1017) of patients. OBV/PTV/r±DSV±RBV was effective and generally well tolerated for treatment of HCV infection in clinical practice.